Numerical analysis of rapid solidification of NiTi alloy: Influence of boundary conditions - Zadravec, Matej; Ternik, Primož; Rudolf, Rebeka; Svetec, Milan (Anali PAZU, 2022)
The objective of the present work is to analyze influence of temperature boundary conditions on the solidification process of NiTi alloy. Alloy is taken as an incompressible fluid where the heat is transferred by conduction and convection, including the thermal phase change phenomenon. The last one is modelled by the improvement procedure, so-called enthalpy-porosity formulation, where the liquid-solid mushy zone is treated as a porous zone with porosity equal to the liquid fraction. The numerical model is based on the finite volume method in body fitted coordinates with a SIMPLER scheme to couple the pressure and velocity fields. Simulation presents solidification for two cooling cases on the cylindrical part, where in the first case the adiabatic boundary condition is considered and in the second case the convective cooling over the wall is present. The results are presented for the velocity and temperature field as well as for the NiTi mass fraction during the solidification process. Results shows that velocity and temperature field is strongly affected by the different cooling condition on the cylindrical wall and therefore the solidification process of the alloy. Analysis shows that cooling on the cylindrical part is one of the major parameters for alloy solidification and therefore should not be neglected.